2020
DOI: 10.1111/bjh.17003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low or high doses of low‐molecular‐weight heparin on thrombin generation and other haemostasis parameters in critically ill patients with COVID‐19

Abstract: The clinical picture of the coronavirus 2 (SARS‐CoV‐2)/COVID‐19‐related acute respiratory syndrome is often associated with a coagulopathy. An elevated D‐dimer has been linked with an unfavorable prognosis in COVID‐19 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…22,23 Moreover, recent reports demonstrated significant ex vivo thrombin generation in the majority of patients with COVID-19 despite anticoagulant therapy, suggesting that before anticoagulation, patients are profoundly hypercoagulable. 18,19,24 This hypercoagulable state is also detected in rotational thromboelastography studies using the EXTEM, which contains a heparin-neutralizing agent. 25 In addition, a hypofibrinolytic state has been demonstrated using whole blood thromboelastography, tissue plasminogen activator-modified thromboelastography, and a plasma-based clot lysis test.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…22,23 Moreover, recent reports demonstrated significant ex vivo thrombin generation in the majority of patients with COVID-19 despite anticoagulant therapy, suggesting that before anticoagulation, patients are profoundly hypercoagulable. 18,19,24 This hypercoagulable state is also detected in rotational thromboelastography studies using the EXTEM, which contains a heparin-neutralizing agent. 25 In addition, a hypofibrinolytic state has been demonstrated using whole blood thromboelastography, tissue plasminogen activator-modified thromboelastography, and a plasma-based clot lysis test.…”
Section: Introductionmentioning
confidence: 85%
“…Several studies demonstrated a hypercoagulable profile by whole blood thromboelastography with conflicting results on the presence of characteristics of disseminated intravascular coagulation 22,23 . Moreover, recent reports demonstrated significant ex vivo thrombin generation in the majority of patients with COVID‐19 despite anticoagulant therapy, suggesting that before anticoagulation, patients are profoundly hypercoagulable 18,19,24 . This hypercoagulable state is also detected in rotational thromboelastography studies using the EXTEM, which contains a heparin‐neutralizing agent 25 .…”
Section: Introductionmentioning
confidence: 99%
“…So far, some in vitro studies have reported that there was a heparin concentration dependent decrease in thrombin generation [120,121]. Studies showed that COVID-19 patients had a higher endogenous thrombin potential [31,39,48,66,[122][123][124][125][126][127]] than manufacturer's reference range, healthy controls or patients with sepsis, sometimes despite UFH or LMWH anticoagulation at a minimum of prophylactic dosing. Few studies found a heparin dose-dependent decrease in thrombin generation [125,127] as described in vitro.…”
Section: Impact Of Differences In Anticoagulation Regimens (Type (Ufhmentioning
confidence: 99%
“…Studies showed that COVID-19 patients had a higher endogenous thrombin potential [31,39,48,66,[122][123][124][125][126][127]] than manufacturer's reference range, healthy controls or patients with sepsis, sometimes despite UFH or LMWH anticoagulation at a minimum of prophylactic dosing. Few studies found a heparin dose-dependent decrease in thrombin generation [125,127] as described in vitro. Interestingly, one study showed that a persisting thrombin burst despite anticoagulation correlated with non-survival [123], whereas another found no difference between noncritical and critically ill COVID-19 patients [124].…”
Section: Impact Of Differences In Anticoagulation Regimens (Type (Ufhmentioning
confidence: 99%
“…Heparin has been widely used in clinic such as thromboembolic diseases, hemodialysis, and cardiovascular surgery (Ayerst et al, 2017;Aslani et al, 2020;Yu et al, 2020). With the advancement of pharmacology and clinical medicine, the application of heparin continues to expand (Chistolini et al, 2020). The negatively charged sulfate groups of heparin can bind and release various positively charged growth factors such as transforming growth factor β (TGF-β) and vascular endothelial growth factor (VEGF) (Jo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%